2018
DOI: 10.1017/cem.2018.271
|View full text |Cite
|
Sign up to set email alerts
|

P073: The GridlockED board game: using serious games for medical education

Abstract: bleeding or abdominal pain, our preliminary results show some patients are not receiving this diagnostic modality nor POCUS during their index ED visit. Particularly in a setting, such as this ED, without rapid access to an early pregnancy clinic, patients should be counselled about their risk of ectopic pregnancy at the time of ED discharge. Keywords: pregnancy, ectopic, ultrasound Introduction: The field of Clinical Informatics (CI) and specifically the electronic health record, has been identified as a key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another paper by Chan et al 25 discussed methods for coaching during chaotic environments, identifying two main types of strategies to teach ED management: (1) workplace‐based methods, including both observation and in situ instruction, and (2) principle‐based advice. Our literature review revealed only two curricula that offered workshops to teach efficiency 2,26 and one board game–themed tabletop simulation 27 …”
Section: Discussionmentioning
confidence: 99%
“…Another paper by Chan et al 25 discussed methods for coaching during chaotic environments, identifying two main types of strategies to teach ED management: (1) workplace‐based methods, including both observation and in situ instruction, and (2) principle‐based advice. Our literature review revealed only two curricula that offered workshops to teach efficiency 2,26 and one board game–themed tabletop simulation 27 …”
Section: Discussionmentioning
confidence: 99%